Germany and the Baltic problem after the Cold War the development of a new Ostpolitik, 1989 - 2000 - Spohr, Kristina 1973- (Routledge, 2004)
"Kristina Spohr Readman scrutinises the development of Germany's new Ostpolitik (eastern policy) in the period 1989-2000. Against the background of recent European history, she analyses the reestablishment of a special relationship between Bonn/Berlin and Moscow. In particular, she assesses the peculiar geopolitical situation of the Baltic states, caught between a turbulent Russia in the east and a unified Germany in the west. The Baltic case reveals the complexities of a post-Cold War European security architecture in the making." "The book will be essential reading for all serious students of contemporary German history and politics."--BOOK JACKET.